Childhood Cancer Survivors: Self-Reported Quality of Life during and after the Cancer Trajectory - Margaretha Stenmarker; Karin Enskär; Maria Björk; Mirka Pinkava; Bo Rolander; Marie Golsäter (Elsevier, 2020)
Objective: This cross-sectional study aimed to present how the unique cancer experience in childhood influences young adults' quality of life (QOL). Methods: Qualitative and quantitative methods were used to code and analyze a study-specific questionnaire (133 items). These data are presented in accordance with a conceptual QOL/health-related QOL model. Results: The participants included 34 women and 28 men (n = 62) diagnosed with solid tumors/lymphoma in the period 1983-2003, who had been treated at the same childhood cancer center in Sweden. The current mean age was 28.7 years (range: 18-45, standard deviation [SD]: 6.3, median value: 28.5), the mean age at diagnosis was 12.9 years (range: 8-17, SD: 2.3, median value: 13), and the mean time elapsed since treatment was 15.7 years (range: 4-28, SD: 2.4, median value: 15). The response rate was 65%. Higher levels of psychological maturity were reported by women versus men (P = 0.01) and by survivors diagnosed with cancer during adolescence versus school age (P = 0.04). Male participants reported lower levels of physical limitations (P = 0.03) and emotional distress when being of treatment and in contact with health care services (P = 0.04). The strongest factor influencing QOL during therapy was parental support (97%), while the strongest factors after therapy were to live a life similar to peers (82%) and to be satisfied with one's life situation (81%). During treatment, limitations influencing QOL were related to lack of school support (2%), and after treatment, to deteriorated relationships with siblings (5%). Conclusions: Life-threatening diseases at young ages have long-term psychosocial effects with ambiguous results at multiple levels. To capture these experiences, we recommend clinical studies that are based on conceptual clarifying frameworks and adopt a quantitative and qualitative research approach.